Former Yugoslav Republic of Macedonia : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Payment Systems, Monetary and Financial Policy Transparency, and Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2003)
The financial system remains vulnerable to weak governance in smaller banks and also to weaknesses in banks' balance sheets. Banking is characterized by high real interest rates, large spreads, and a limited appetite for lending. Stress tests indicate that the banking system is relatively resilient to the direct effects of individual shocks, with credit risk having the greatest impact. Deficiencies in the framework for banks' liquidity management are developmental in nature but need to be addressed to avoid systemic problems.